Concordance between physiological arousal and emotion expression during fear in young children with autism spectrum disorders - Zantinge, Gemma (Autism, 2018)
This study aimed to measure emotional expression and physiological arousal in response to fear in 21 children with autism spectrum disorders (43–75 months) and 45 typically developing children (41–81 months). Expressions of facial and bodily fear and heart rate arousal were simultaneously measured in response to a remote controlled robot (Laboratory Temperament Assessment Battery). Heart rate analyses revealed a main effect of task from baseline to fear (p < 0.001, [Formula: see text]), no interaction effect and no effect for group. In addition, children with autism spectrum disorder showed intact facial and bodily expressions of fearful affect compared to typically developing children. With regard to the relationship between expression and arousal, the results provided evidence for concordance between expression and arousal in typically developing children (r = 0.45, n = 45, p < 0.01). For children with autism spectrum disorder, no significant correlation was found (r = 0.20, n = 21, p = 0.38). A moderation analysis revealed no significant interaction between expression and arousal for children with and without autism spectrum disorder (F(1, 62) = 1.23, p = 0.27, [Formula: see text]), which might be the result of limited power. The current results give reason to further study concordance between expression and arousal in early autism spectrum disorder. Discordance might significantly impact social functioning and is an important topic in light of both early identification and treatment.